The association of preoperative blood markers with postoperative readmissions following arthroplasty. (2021) - Khoshbin, A.; Hoit, G.; Nowak, L. L.; Daud, A.; Steiner, M.; Juni, P.; Ravi, B.; Atrey, A.
No abstract available